Impact des Processus Hydrochimique sur la Qualité des Eaux souterraines de la Ville de N’Djaména-Tchad - Edith, Kadjangaba; DaїraDjoret; Jean-Claude, Doumnang Mbaigane; Anaclet, Ndoutamia Guelmbaye; Yaya, Mahmout (European Scientific Journal, ESJ, 2018)
The problem of access to water in quality and quantity is a major challenge, because it strongly influences the socio-economic conditions of populations in developing countries. The water of the basement of the city of N’Djamena is not sheltered from the risk of pollution. She disposes very little functional wastewater disposal system because the collection networks are almost non-existent, moreover there is a lack of infrastructures for evacuation of household waste, as well as the solid waste treatment units. In addition, under the town of N’Djamena there are two main aquifers located respectively at about 10 and 60 m depth, and the presence of an intermediate aquifer about 30 m deep was also noted. Like all urban cities, these aquifers are not immune to the risks associated with human activities. In order to highlight the influence of the hydrochemical process on the groundwater quality of the city of N’Djamena, a study was conducted on a sample of well water and borehole. In total, 20 open wells and 16 boreholes were sampled and analyzed. The pH and the temperature were measured in situ using the pH 323 / Set B mixed electrode and the conductivity using the Lf 318 / Set electrode. It is the same for the alkalinity which is determined by titrimetry, using a HACH / 16900 brand digital titrator. The analysis of major ions was carried out at the Laboratory of Hydrogeology of the University of Avignon. the anions (Cl - , SO42- , NO3 - ) were analyzed using a Dionex ion chromatograph, and the cations (Ca2+ , Mg2+ , Na+ , K + ) using an atomic absorption spectrometer for with a relative uncertainty of 5%. The results of the in-situ parameters have shown that the waters have a pH which is around 6.85 in the wells and 7.24 in the boreholes and the measured temperature is close to the ambient temperature of the air which is 28 ° C. The mineralization of the waters is sometimes high and this results in values of conductivities that can reach 1253 μS / cm), especially in the wells. This increase in conductivity is accompanied by an increase in Cl - and NO3 - ions in the water. Groundwater has a wide variety of chemical facies, among which mention may be made of calciumbicarbonate-type water, sometimes nitrated, sodium bicarbonate and potassium and nitrate, which may have high chloride contents and bicarbonate and chloride and nitrate calcium or sodium. Principal Component Analysis (PCA) has shown that the main processes influencing groundwater chemistry are hydrolysis of silicates, cation exchange between groundwater and clayey minerals, evaporation and the impact of human activities.